English as a Foreign Language (EFL) Students’ Ability in Identifying Moral Values within Narrative Texts - Yunita, Widia; Patriadi, Patriadi (Universitas Lancang Kuning, 2019)
The aimed of the research is to find out the students’ ability in identifying moral values of narrative text. The research design of this research was a descpritive quantitative. The researcher analyzed the data from students’ test and on the data analysis, the researcher has got result from the students’ test, there are: The students who got excellent level is 0 (0%), very good level is 29 (60%), good 13 (28%) and 6 come into fair level (12%), while 0 students got poor level (0%). The means score of the students’ test is 77, it means that the students’ ability in identifying moral values of narrative text is Good